2021
DOI: 10.1177/1352458521993075
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization provides no evidence for a causal role in the bidirectional relationship between depression and multiple sclerosis

Abstract: Background: Major depressive disorder (MDD) is common in multiple sclerosis (MS) and its incidence rises before MS diagnosis. However, the causality and direction of this association remain unclear. Objective: The objective is to investigate the bidirectional relationship between MS and MDD using Mendelian randomization (MR). Methods: We selected genetic instruments associated with risk of MDD ( n = 660,937 cases; 1,453,489 controls) and MS ( n = 47,429 cases; 68,374 controls). Using two-sample MR, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In addition, PRS for BMI was the only trait which remained statistically significant following the adjustment for additional potential confounders, such as age and sex. The link between BMI and depression in the general population is well-established, with a Mendelian randomization study suggesting that higher BMI partly causes depression [ 23 , 24 , 43 ]. Our stratified regression analysis further identified that the BMI PRS was significantly associated with the higher depressive symptom group in the IMID sample but was no longer significant in the non-IMID/psychiatric sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PRS for BMI was the only trait which remained statistically significant following the adjustment for additional potential confounders, such as age and sex. The link between BMI and depression in the general population is well-established, with a Mendelian randomization study suggesting that higher BMI partly causes depression [ 23 , 24 , 43 ]. Our stratified regression analysis further identified that the BMI PRS was significantly associated with the higher depressive symptom group in the IMID sample but was no longer significant in the non-IMID/psychiatric sample.…”
Section: Discussionmentioning
confidence: 99%
“…We performed complementary mediation analysis to test whether IMID mediates the association between BMI PRS and depressive symptoms trajectories. We expected that we would not observe mediation based on prior Mendelian randomization studies suggesting BMI is causally related to IMID and to MDD, but IMID is not causally associated to MDD [ 24 28 ] ( Fig. S2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR has been applied to MS, providing evidence for causal roles of high BMI [10][11][12][13] , increased interleukin-6 (IL-6) signaling 11 , and low vitamin D 10,13 . On the other hand, MR did not support the causal roles of uric acid 14 , leptin 13 , adiponectin 13 , and depression 15,16 . A systemic MR study of 65 possible risk factors for MS revealed robust evidence of causality for four of them, high childhood and adult BMI, low vitamin D, and low physical activity.…”
Section: Introductionmentioning
confidence: 83%
“…Apolipoprotein ε*2 has been attributed to have a protective role since this allele has been found to correlate with less depressive symptoms [33], but these findings have not been validated further. A recent study investigating the relationship between depression and MS using mendelian randomization came to conclusion that there is no causal contribution between depression genetic liability and MS susceptibility and vice versa [34].…”
Section: Geneticsmentioning
confidence: 99%